Liuwei Dihuang pills ameliorate renal injury in experimental type 2 diabetes mellitus rat by regulating host-gut microbiota interaction - Jiang, Han; Hu, Xiao-wan; Deng, Xu; Huang, Xian-jie; Chen, Yu-lin; Yang, Yi-fan; Du, Yan; Ji, Shuai; Tang, Dao-quan (Frontiers in Pharmacology, 2026)
BackgroundLiuwei Dihuang pills (LW) are widely used as the traditional tonic prescription for the treatment of diabetes and diabetic kidney disease (DKD). This study aimed to investigate the potential mechanism underlying LW-mediated prevention and treatment of DKD from the perspective of host-gut microbiome co-metabolism.MethodsA rat model of DKD was established using high-fat diet and streptozotocin. Levels of type IV collagen (Col IV), fibronectin (FN), laminin (Lam), transforming growth factor-β (TGF-β), SMAD family member 7 (SMAD7), and SMAD3 in the kidneys were determined by real time-polymerase chain reaction and Western blot. Fecal metabolites were profiled using ultra-high-performance liquid chromatography-tandem mass spectrometry. Metagenomic sequencing of the feces was performed using high-throughput sequencing.ResultsWhen combined with metformin (MET)-based therapy, LW significantly improved serum creatinine and blood urea nitrogen levels, kidney index, 24-h urine volume, urine protein content and excretion rate, and urinary creatinine and cystatin C levels. It also attenuated morphological changes. Correspondingly, LW intervention reduced the renal expression of TGF-β, SMAD3, Col IV, LAM, FN, interleukin (IL)-6, and IL-1β, while increasing SMAD7 expression. Additionally, it normalized metabolic pathway abnormalities in galactose, butyric acid, fructose, mannose, amino sugar, and nucleotide sugar metabolism. Moreover, LW regulated bacterial imbalances, notably in specific species such as Allobaculum unclassified, Escherichia coli, Pseudoflavonifractor capillosus, Desulfovibrio porci, Oscillibacter sp. CU971, Parablautia muri, Phocaeicola dorei, Phocaeicola faecalis, Phocaeicola vulgatus, and Raoultella unclassified.ConclusionThe combination of LW and MET ameliorated renal impairment in DKD rats by regulating the TGF-β/SMAD signaling pathway, metabolic disturbances in endogenous metabolites, and gut microbiota dysbiosis.